APLIKASI ILUSTRASI KOMIKAL PADA GAYA BOBODORAN SUNDA KANG IBING - Umri, Gilang Abiogi (LPPM BSI Bandung, 2015)
ABSTRACTFinal Project aims to entertain and hopefully can be used as a historical knowledge about the Sunda bobodoran pioneer . By taking the title